EKSISTENSI GARANSI BANK DAN SURETY BOND - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
The material for the writing of this publication on the Existence of Bank Guarantees and Surety Bonds in the Implementation of Contractual Agreements on Public Construction Projects were obtained through a study of normative law. This research aims to find out the legal status of Bank collaterals and Surety Bonds as securities in the implementation of contractual agreements on public construction projects as well as the reasons for the differences in the payment of claims for liquidation of these two types of security.According to Act Number 7 of 1992 concerning Banking, a collateral is part of a Bank s business undertaking, while a Surety Bond, according to Government Regulation Number 34 of 1978, is a business undertaking by the Jasa Raharja Insurance Corporation Ltd. Under Presidential Decision Number 16 of 1994 concerning the National Budget, Bank Guaran cc:, and Surety Bonds are both used as securities for contractual works funded by the Government.The primary and secondary data for this research were collected through library research and field research which comprised documentary study, questionnaires, and interviews.From the result of the analysis made through a qualitative method, it is found that the legal status of a Bank guarantee in the implementation of a contractual agreement on a public construction project offers an assurance for the holder's right in the sense that the completion of a project guaranteed by a Bank Guarantee can be achieved in accordance with the agreemerit because the payment of a claim of liquidation can be made immediately as such as the amount that a Bank guarantee is worth. On the other hand, the legal status of a Surety Bond does not offer the same assurance for the holder's right because the completion of a project guaranteed by a Surety Bond may be hindered if the contractor defaults (on the project). This can happen because the payment of a claim for liquidation is based on the amount of the actual loss suffered by the holder and is limited to the maximum amount that the Surety Bond is worth. The payment of a claim for liquidation of a Bank guarantee differs from that of a Surety Bond because each has a different legal basis. A Bank guarantee is based on the law of security (Borgtocht) while a Surety Bond is based on the Iaw of Liability Insurance.